THE ROLE OF COMMUNICATION IN THE BUYING AND NEGOTIATION PROCESS - Oktri Permata Lani (Alfuad: Jurnal Sosial Keagamaan, 2021)
Individuals and individuals who are members of an organization cannot achieve their goals and cannot even carry out their lives if they do not cooperate with other parties. Today, competition among companies in Indonesia is growing, especially in the sale of cars and spare parts. These symptoms can be seen from the price competition for cars and spare parts which vary greatly from one company to another, namely from low prices with standard quality to high prices with good quality. This is what makes a company compete to improve the quality of basic car materials and spare parts at prices that are affordable by the community. Negotiation is a process of interaction in an offer made by two or more parties, who want to achieve their respective interests and realize that in order to achieve all of their interests, they must relate to each other and direct each other's interests in order to achieve the benefit of all parties. In this case, the agreement between the two parties on the price quote is carried out by the customer and the company's negotiator. Based on the background of the problem described above, the authors formulate the main problem as follows: "What is the role of communication in the process of buying and selling negotiations". From the formulation of the problem that has been described above, the researcher wants to achieve a goal in this study. The purpose of this research, is to determine the role of communication in the process of buying and selling negotiations and to determine the barriers to communication. This research method uses a literature review. Communication is a process, namely the process of conveying thoughts or feelings by someone (the communicator) to another person (the communicant) to change the opinions, attitudes and behavior of others. By communicating, humans can convey their experiences, desires, and feelings to others directly or through the means or media they have. Through communication individuals can plan their future, form groups for cooperation, convey information, opinions, ideas, concepts, knowledge and change attitudes. To achieve effective and efficient negotiations is not as easy as people imagine. Many things must be considered in communicating so that messages or statements conveyed to others can be understood and understood.